2021
DOI: 10.1101/2021.02.20.432046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced binding and neutralization of infection- and vaccine-induced antibodies to the B.1.351 (South African) SARS-CoV-2 variant

Abstract: The emergence of SARS-CoV-2 variants with mutations in the spike protein is raising concerns about the efficacy of infection- or vaccine-induced antibodies to neutralize these variants. We compared antibody binding and live virus neutralization of sera from naturally infected and spike mRNA vaccinated individuals against a circulating SARS-CoV-2 B.1 variant and the emerging B.1.351 variant. In acutely-infected (5-19 days post-symptom onset), convalescent COVID-19 individuals (through 8 months post-symptom onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…If the number of positive safety reports were to be increased in the coming months, one could expect that anxiety and fear towards adverse event would decrease. Other components such as efficacy, and length of immunization, would become more relevant, especially in light of the emergence of variants of concerns and recombining viruses [39,40]. Most (60%) professionals were hesitant towards vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…If the number of positive safety reports were to be increased in the coming months, one could expect that anxiety and fear towards adverse event would decrease. Other components such as efficacy, and length of immunization, would become more relevant, especially in light of the emergence of variants of concerns and recombining viruses [39,40]. Most (60%) professionals were hesitant towards vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 is an enveloped, positive-sense, singlestranded RNA beta-coronavirus, being prone to mutate very rapidly, since during RNA replication no error-correction mechanisms is used when copying the RNA genetic information into DNA [25][26][27][28]. Such mutations can confer new features to the virus, including the ability to infect new types of cells, or even new organisms and thus to determine the spillover, and this phenomenon occurred extensively in the case of SARS-CoV-2, as already mentioned here [11][12][13]. Like the preceding two CoVs that provoked outbreaks, SARS-CoV and MERS-CoV, the genome of SARS-CoV-2 encodes for several non-structural proteins (nsps), including several enzymes, such as an RNA-dependent RNA polymerase (RdRp), a helicase, a 3-chymotrypsin-like protease, also known as main protease (MPro) and a papain-like protease (PLP).…”
Section: Coronavirusesmentioning
confidence: 89%
“…The monoclonal antibodies (MAbs) constitute another therapeutic approach that is being pursued, with some highly effective ones discovered from plasma of convalescent COVID-19 patients, now in clinical trials [11]. However, although vaccines and MAbs already showed their efficacy and will definitely be useful to stop or at least slow down the pandemic, the continuous evolution of the virus, which uses a variety of immune escape mechanisms, will probably lead to the emergence of variants which are not neutralized by these agents, as already reported for the South African and Brazilian SARS-CoV-2 strains [12,13]. For these reasons, novel small molecule antiviral drugs capable of impairing the replication of CoV that can be used in the current outbreak and maybe also in future occurrences, are in exceedingly high demand but are scarcely available to date [14].…”
Section: Coronavirusesmentioning
confidence: 98%
“…SARS-CoV-2 strain analysis in participants in Phase 3 studies in South Africa has revealed that some vaccines show diminished protection against the B.1.351 variant strain, 17 including ChAdOx, 18 NVX-CoV2373, 19,20 and Ad26.COV2-S. 21 In addition, in vitro studies show that wild type S-specific antibodies elicited by mRNA-1273 and BNT162b1 show reduced binding to the B.1.351 variant S protein. [22][23][24] Taken together, these findings raise the concern that monovalent vaccines targeting only the S protein may not be the most optimal strategy for conferring protection against continually emerging variants. SARS-CoV-2 expresses a number of other immunogenic proteins that may induce protective antibody and/or T cell responses.…”
Section: Introductionmentioning
confidence: 99%